The Role of Social Capital in the Successful Implementation of Resilient Villages: A Case Study of Jetak Lor Hamlet, Malang Regency - Salam, Abdus; Sihidi, Iradhad Taqwa; Basriyah, Unika (Sospol, 2025)
Covid-19 has significantly impacted the economic well-being of communities. In response, the Jetak Lor Hamlet government initiated a “Resilient Village” program through Jimpitan Beras and Pasar Gandul, aiming to support food security. This study explores how social capital operates in the implementation of this concept, using Robert MZ Lawang's theory, which emphasizes trust, social networks, and norms. Employing a qualitative descriptive method, data were collected through interviews, observations, and documentation, and analyzed using coding and triangulation. The findings reveal that these programs were effective due to strong social capital, especially community solidarity. Despite limited participation from approximately 30% of residents, the study highlights how social capital is essential in managing crises and can inform future policies. This research contributes to literature on community resilience and offers practical insights for local governance and disaster response frameworks.